2016
DOI: 10.1097/tld.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Writing Instruction and Self-Regulation for Students With Autism Spectrum Disorders

Abstract: Children with autism spectrum disorders (ASDs) may struggle to self-regulate their learning, and such difficulty may be especially notable in the area of written expression. One intervention that has explored self-regulation in writing is the self-regulated strategy development (SRSD) approach. In this article, a review of the research using SRSD to teach children with ASD to write is conducted. Investigation yielded 11 studies including 27 participants with ASD. Results of the review indicated that students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…From an executive function perspective, Jack may have experienced difficulties in self-regulating his behaviors for the task or adopted self-directed goals rather than task-specific goals. Perhaps selfmanagement instruction would help Jack stay on topic and be mindful of his audience more so than the prompting used in this intervention (e.g., Asaro-Saddler, 2016). From a motivational perspective, Jack may have preferred writing about his own interests compared to topics offered by the computer.…”
Section: Research Aim 3: Response To Computerized Instruction For Permentioning
confidence: 99%
“…From an executive function perspective, Jack may have experienced difficulties in self-regulating his behaviors for the task or adopted self-directed goals rather than task-specific goals. Perhaps selfmanagement instruction would help Jack stay on topic and be mindful of his audience more so than the prompting used in this intervention (e.g., Asaro-Saddler, 2016). From a motivational perspective, Jack may have preferred writing about his own interests compared to topics offered by the computer.…”
Section: Research Aim 3: Response To Computerized Instruction For Permentioning
confidence: 99%
“…The authors compared three persuasive baseline essays with three post-intervention texts and found evident improvements, both in qualitative and quantitative aspects, which gives support to the effectiveness of the POW + TREE approach. Asaro-Saddler [18], after reviewing 11 studies investigating the specific strategy of SRSD used in the writing instruction of learners with ASD, found that these students improved their planning ability, the number of written elements, and the content of their writing when using the self-regulated strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Prior reviews of writing intervention for students with ASD have not included handwriting studies-instead focusing on spelling and sentence construction (Pennington & Delano, 2012) or self-regulated strategy instruction for composition (Asaro-Saddler, 2016). Four prior studies (Batchelder, McLaughlin, Weber, Derby, & Gow, 2009;Cosby, McLaughlin, & Derby, 2009;Harris, Little, & Akin-Little, 2017; Moore et al, 2013) have applied handwriting intervention for students with ASD using various forms of antecedent instruction and consequence-based procedures.…”
Section: Prior Research On Handwriting Intervention For Students Withmentioning
confidence: 99%
“…Research has described various specific difficulties with speed, spacing, alignment (Hellinckx et al, 2013) and size (Rosenblum et al, 2016). Considering the tendency of students with ASD to use unsophisticated sentence structure (Myles et al, 2003) and produce shorter, lower quality composition (Brown et al, 2014;Zajic et al, 2018), it is not surprising that most intervention research has focused on spelling, sentence construction, or extended composition for this population (Asaro-Saddler, 2016;Pennington & Delano, 2012). The published literature available on handwriting interventions for students with ASD has been narrow in scope: A total of four studies have targeted acquisition of accurate handwriting within first names of one adolescent (Batchelder et al, 2009) and five early elementary students (Cosby et al, 2009;Harris et al, 2017;Moore et al, 2013).…”
Section: Handwriting Interventions For Students With Autism Spectrum mentioning
confidence: 99%
See 1 more Smart Citation